THE IMPACT OF EMERGING TRENDS IN THE "MAKE IN INDIA" PROGRAM ON THE INDIAN ECONOMY - Dangi, Vishnu Prasad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Make in India is an initiative of the Government of India to encourage multi-national, as well as domestic companies to manufacture their products in India. Make in India Campaign was launched by the Prime Minister Narendra Modi on 25 September 2014 by addressing a mass audience including both national and international entrepreneurs in New Delhi.